In vitro probiotic properties of Pediococcus pentosaceus L1 and its effects on enterotoxigenic Escherichia coli-induced inflammatory responses in porcine intestinal epithelial cells. (July 2020) - Yin, Huajuan; Ye, Pengfei; Lei, Qingzhi; Cheng, Yandong; Yu, Hang; Du, Jinjing; Pan, Hongbin; Cao, Zhenhui
Abstract: This study aimed to evaluate in vitro probiotic characteristics of Pediococcus pentosaceus strain L1 from pickled radish and investigate its impacts on inflammatory responses in porcine intestinal epithelial cells (IEC) to enterotoxigenic Escherichia coli (ETEC) F4 + . The abilities of P. pentosaceus L1 to tolerate gastrointestinal conditions and to antagonize ETEC F4 + growth were determined. Adhesion of P. pentosaceus L1 and its effect on ETEC F4 + adhesion to porcine IPEC-J2 IEC were evaluated. Furthermore, the effects of this strain on proinflammatory gene expression and cytokines/chemokine production in porcine IPEC-J2 IEC induced by ETEC F4 + were determined. P. pentosaceus L 1 showed good tolerance to the medium adjusted at pH 2.5 and consequently supplemented with 0.3% oxgall. Reduction of ETEC F4 + growth in co-culture with L1 was found. Effective adhesion of L1 to porcine. IPEC-J2 IEC was observed under these conditions. P. pentosaceus L1 decreased the adhesion of ETEC F4 + to IPEC-J2 IEC and the extent of inhibition of ETEC F4 + adhesion depended on the timing of L1 addition. Further analysis revealed down-regulation of expression of ETEC F4 + -induced proinflammatory genes encoding interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), and interleukin-8 (IL-8) in IPEC-J2 IEC. Expression of the genes involved in NF-κB pathway, including RELA and NFKB1, were also repressed, as was production of IL-6, TNF-α, and IL-8. These results indicate that P. pentosaceus L1 may have potential as a probiotic for control of ETEC infection in pigs. Highlights: Pediococcus pentosaceus L1 showed good tolerance to low pH and bile salts. P. pentosaceus L1 antagonized growth of enterotoxigenic Escheichia coli （ETEC）F4 + . P. pentosaceus L1 could adhere to IPEC-J2 intestinal epithelial cells (IEC) and reduce ETEC F4 + adhesion to IPEC-J2 IEC. P. pentosaceus L1 reduced IPEC-J2 IEC proinflammatory response to ETEC F4 + via down-modulating NF-κB signaling.